Functional immune cell-astrocyte interactions - Sanmarco, Liliana M; Polonio, Carolina M; Wheeler, Michael A; Quintana, Francisco J (The Journal of experimental medicine, 2021)
Astrocytes are abundant glial cells in the central nervous system (CNS) that control multiple aspects of health and disease. Through their interactions with components of the blood-brain barrier (BBB), astrocytes not only regulate BBB function, they also sense molecules produced by peripheral immune cells, including cytokines. Here, we review the interactions between immune cells and astrocytes and their roles in health and neurological diseases, with a special focus on multiple sclerosis (MS). We highlight known pathways that participate in astrocyte crosstalk with microglia, NK cells, T cells, and other cell types; their contribution to the pathogenesis of neurological diseases; and their potential value as therapeutic targets.